2008
DOI: 10.1007/s00442-007-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Florivory affects pollinator visitation and female fitness in Nemophila menziesii

Abstract: While herbivory has traditionally been studied as damage to leaves, florivory - herbivory to flowers prior to seed set - can also have large effects on plant fitness. Florivory can decrease fitness directly, either through the destruction of gametes or through alterations to plant physiology during fruit set, and can also change the appearance of a flower, deterring pollinators and reducing seed set. In order to distinguish between these hypotheses, it is necessary to both damage flowers and add pollen in exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
5
35
1
4
Order By: Relevance
“…This study revealed that pollinators were less likely to visit and pollinate flowers with missing parts (especially the lower lip), resulting in lower fruit and seed sets. Both naturally and artificially damaged flowers of Nemophila menziesii receive fewer visits from pollinators and set less fruit and seed than do undamaged flowers (McCall 2008).…”
Section: Floral Herbivorymentioning
confidence: 99%
“…This study revealed that pollinators were less likely to visit and pollinate flowers with missing parts (especially the lower lip), resulting in lower fruit and seed sets. Both naturally and artificially damaged flowers of Nemophila menziesii receive fewer visits from pollinators and set less fruit and seed than do undamaged flowers (McCall 2008).…”
Section: Floral Herbivorymentioning
confidence: 99%
“…First, floral herbivory affects the abundance and appearance of flowers, and may alter patterns of pollinator attraction and pollen movements Leavitt and Robertson 2006;Penet et al 2009). Second, floral herbivory may directly reduce the availability of reproductive organs that would otherwise produce mature seeds (McCall 2008). Finally, temporal changes in the intensity of floral herbivory have been observed (Evans et al 1989;EnglishLoeb and Karban 1992;Bishop and Schemske 1998;Pilson 2000;Mahoro 2002;Juenger et al 2005;Tarayre et al 2007;Oguro and Sakai 2009), and this can serve as a source of selection on flowering time to avoid floral herbivory (Elzinga et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…But, they can also cause collateral damage by altering species interactions, such as plant–pollinator interactions when florivores reduce flower numbers or size (Lohman et al . ; see Appendix S1 in Supporting Information), or more directly by damaging petals, which alters floral shape and size (McCall ; Sober et al . ), or simply by being present on a flower (Lohman et al .…”
Section: Introductionmentioning
confidence: 99%